Pemanfataan Aplikasi Canva Sebagai Media Desain Promosi Produk Bagi Guru SDN 18 Kampung Durian - Juli Adevia; Nova Suryani; Oza Syafriani; Defri Rahman; Muhammad Ilham; Ahmad Fachri; Muhammad Farrasky Delas Putra; Yozi Putri Sakinah; Sultani Sultani; Ramadhi Ramadhi; Barkhia Yunas; Oktia Verinda; Allia Nabila (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The community service program titled "Utilization of Canva Application as a Promotional Design Media for Teachers of SDN 18 Kampung Durian" aims to enhance the graphic design skills of teachers through intensive training using the Canva application. This program was implemented to address the challenges faced by teachers in promoting their side business products and creating engaging teaching materials. Through lectures, discussions, Q&A sessions, and intensive mentoring, the program successfully improved the technical abilities of the teachers in using Canva. Evaluation results show that 85% of the teachers feel more confident and capable of producing more professional designs. This program also positively impacted the quality of school promotional materials and the teachers' side businesses, as well as increased their technological literacy and creativity. In conclusion, this training successfully achieved its goals and made a positive contribution to enhancing the quality of education and economic welfare of the teachers at SDN 18 Kampung Durian.